Cluster Decay Half-Lives of 156-162Hf Isotopes Using the Woods-Saxon Potential Model. - K. Gado
Decay half-lives are evaluated in the framework of a Woods-Saxon potential model for various clusters decay. In this model cluster -decay are considered as penetration of the cluster-particle through the potential barrier formed by the nuclear, Coulomb, and centrifugal interactions between the cluster - particle and core. The spins and parities of the parent and core nuclei as well as the quadruple deformations of the core nuclei are taken into account for evaluation of the cluster-decay half-lives. The cluster -decay half-lives for isotopes nuclei156-162Hf agree well with the experimental data.
Keywords: Physics; Nuclear physics